The Goths & Other Stories - Zamler-Carhart, Sasha (punctum books, 2020)
"In the winter of 476 A.D. the Ostrogoths, hungry and exhausted from wandering for months along the barren confines of the Byzantine Empire, wrote to Emperor Zeno in Constantinople requesting permission to enter the walled city of Epidaurum and just kinda crash and charge their phones. Closer to home, Orpheus walks Eurydice through a suburban refrigerator as a matter of tax planning. In The Goths & Other Stories, sexual desire, food, space, and anger are distorted; prose fiction, experimental poetry, philosophy, and design theory intersect and breed. The poetics of car accidents, capitalist consumption, and anarchist terrorism unfold at a Southern California car dealership. Readers of all centuries will feel at home in this book. The smell of seafood and speculative urban planning merge into a 1990s computer game, Abidjan has 12,756 streets with no way to go from one to another, an apocalypse of tax law and classical mythology descends upon suburbia and reveals a medieval theology of design, theater, and light. The book's six stories are set in different times and places - sometimes within the same narrative - but have in common a slippery approach to the boundaries between fiction and theory, between ontological planes, between the comical and the moral. Together they also form a treatise on the nature of writing as a branch of design - one whose medium is easier to reveal than to define."